Cultural determinants of nationally specific metaphorical models in Russian and Spanish slang - Abdullaev , Marks Kamilzhanovich (The Lingua Spectrum, 2026)
This article presents a comparative analysis of cultural determinants shaping metaphorical models in Russian and Spanish slang. Despite a substantial body of cognitive linguistics research, cultural conditioning of metaphorisation in substandard vocabulary of these two languages remains underexplored. The study's novelty lies in describing the hierarchical organisation of cultural determinants that generate nationally specific metaphorical models. A corpus of 4,199 units was compiled via systematic sampling from authoritative lexicographic sources (1,970 Russian; 2,229 Spanish); the MIPVU metaphor identification procedure and frame analysis were applied. Results show that archetypal schemas CONTAINER, PATH, and FORCE cover 85-89% of the material in both languages, while nationally specific frames account for approximately 30% of the corpus. Dominant cultural determinants in Russian slang are ROAD, HOME, FREEDOM, and FATE; in Spanish – HONOUR, PASSION, DEATH, and FESTIVITY. The findings verify Extended Conceptual Metaphor Theory and clarify the mechanism of cultural filters operating at the level of conceptual domains. Results are applicable to lexicographic practice, the methodology of teaching Spanish and Russian as foreign languages, as well as to the theory and practice of intercultural communication.